Comparison of Sodium Acid Sulfate and UV-C Treatment on Browning and Storage Quality of Fresh-Cut Potatoes. (30th July 2017) - Xie, Yajing; Lin, Qiong; Guan, Wenqiang; Cheng, Shuzhen; Wang, Zhidong; Sun, Chongde
Abstract : Fresh-cut vegetables, such as potato chips, get brown quickly and can easily be infected by bacterium during storage. Sodium acid sulfate (SAS) and UV-C treatments are regarded as effective methods for food preservation. In this study, the effects of SAS, UV-C treatment, and their combination on fresh-cut potatoes during storage were evaluated. Compared with the control, all of the treatments were effective in inhibiting the bacterial growth during the whole storage period. Also, both SAS and SAS + UV-C treatments significantly decreased browning and polyphenol oxidase (PPO) activity and increased the firmness and malondialdehyde (MDA) contents, while the UV-C treatment has no good effects on protecting such storage qualities in fresh-cut potatoes. However, when compared with SAS treatment, the combination of SAS and UV-C treatment did not promote the effect in protecting the storage abilities. Thus, it was concluded that SAS is a better treatment in extending shelf life and controlling the quality of fresh-cut potatoes during storage compared to UV-C treatment.